Didattica della Chimica: un’esperienza all’Università di Parma - Rogolino, Dominga (Chimica nella Scuola, 2024)
The birth of a chemistry education course is a complex process that requires the ability to draw ideas and teaching approaches from a vast literature and adapt them to the needs of the operating environment. This contribution describes how the chemistry education course at the University of Parma was conceived and organized. The sharing of teaching-related experiences serves as a source of enrichment and reflection in anticipation of the challenges that lie ahead in designing impactful and meaningful educational courses.